2018
DOI: 10.1111/cob.12248
|View full text |Cite
|
Sign up to set email alerts
|

Beyond lifestyle interventions: exploring the potential of anti‐obesity medications in the UK

Abstract: SummaryIn the UK, over one‐quarter of the adult population have obesity (body mass index ≥30 kg m−2). This has major implications for patients’ health and the National Health Service. Despite published studies showing that significant weight loss can be achieved and maintained in primary care, and guidance from the National Institute for Health and Care Excellence, weight management services are inconsistently implemented. This may be due primarily to workload and financial constraints. There is also a lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In our study, orlistat therapy achieved a lower WL than that observed in RCTs. This gap between a real‐world setting and a clinical trial setting has also been reported in other observational studies with orlistat and it may be because of several factors affecting the external validity of RCTs, such as restrictive inclusion criteria that exclude individuals with potential poor tolerability to the drug or patients with severe comorbidities and differences between the trial protocol and routine clinical practice leading to a more frequent contact with the multidisciplinary team and a better adherence in RCTs . A retrospective analysis of data from the UK Clinical Practice Research Datalink, including 100 701 patients receiving orlistat, showed a mean WL of 2.5 kg 1 year from baseline, with gains of 1.9 kg in year 2 and 0.3 kg in year 3, resulting in an overall reduction of 0.3 kg by the end of year 3 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our study, orlistat therapy achieved a lower WL than that observed in RCTs. This gap between a real‐world setting and a clinical trial setting has also been reported in other observational studies with orlistat and it may be because of several factors affecting the external validity of RCTs, such as restrictive inclusion criteria that exclude individuals with potential poor tolerability to the drug or patients with severe comorbidities and differences between the trial protocol and routine clinical practice leading to a more frequent contact with the multidisciplinary team and a better adherence in RCTs . A retrospective analysis of data from the UK Clinical Practice Research Datalink, including 100 701 patients receiving orlistat, showed a mean WL of 2.5 kg 1 year from baseline, with gains of 1.9 kg in year 2 and 0.3 kg in year 3, resulting in an overall reduction of 0.3 kg by the end of year 3 .…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the high rate of WD with both drugs could lead to overestimation of the effect on weight and underestimation of AEs; unfortunately this is a frequent issue in both RCTs and RWS with WLMs. Selection bias is another potential limitation; however, WLMs in Spain, as in in other European countries, are rarely used in primary care, and their prescription is usually restricted to patients with severe obesity in specialist clinics. Finally, differences in WL between liraglutide and orlistat may have been underestimated because very few individuals reached the maximum dose of liraglutide at the end of the follow‐up because of its high cost.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies with liraglutide 3 mg and other obesity medications will have to assess long-term cost-effectiveness and the budgetary impact of using these medications to address not only body weight loss, but also the effects upon various obesity-related comorbidities. 15 The strengths of our data include the large number of patients, the detailed documentation of follow-up, and the routine clinical practice setting from a single centre. Thus, the findings are probably generalizable to other routine care clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle interventions are considered cornerstones for the management of obesity 7. Despite the impressive results from intensive lifestyle interventions in Look Ahead study,8 and more recently the Diabetes Remission Clinical Trial (DIRECT) and Counterweight-Plus studies,9 10 which used intensive and structured weight management programmes to achieve weight loss and T2D remission in real-life community settings, lifestyle interventions still commonly only achieve an average of 5% wt loss11 12 and long-term weight maintenance remains a challenge 13 14.…”
Section: Introductionmentioning
confidence: 99%
“…Maximal benefits for the treatment of obesity-associated complications are obtained with weight loss above 15% 15. Pharmacotherapy for obesity can support some people to achieve these results,16–18 but currently it is not used frequently enough to be considered a cornerstone treatment 7…”
Section: Introductionmentioning
confidence: 99%